ARTIFICIAL LIFE MODEL PERTUMBUHAN TANAMAN PADAVARIETAS KEDELAI DENGAN PENGARUH PEMBERIAN KOMPOSISI PUPUK GUNA PENINGKATAN PRODUKTIFITAS HASll PANEN - , Atris Suyantohadi ([Yogyakarta] : Lembaga Penelitian dan Pengabdian Kepada Masyaraka, 2009)
The approach on examining the natural process had been analyzed and synthesized through modeling in artificial life. The research aimed to visualize and design the plant growth on the soybean varieties through artificial life by using artificial neural network (ANN) and Undenmayer System (L-System) method. Based on the treatment of plant fertilizer composition in the experimental research and plant growth modeting, the highest production of soybean varieties Dhetam 2 compared to Cikuray, Burangrang, and Malikawith the use of manure fertilizer of Nitrogen (N),Phosphor (P) and Potassium (I&lt